About conditions of effective interaction of waves in non-uniform, non-stationary and nonlinear medium - Buts, V.A. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
It is shown that in the distributed systems there are more general conditions for effective interaction of waves (synchronism) than the well known conditions. The well known conditions of synchronism are just the particular case of these more general conditions. It has been shown that these new conditions lead to new opportunities for effective interaction of wave, particularly at interaction of waves in plasma. Показано, что в распределенных системах существуют более общие условия эффективного взаимодействия волн (синхронизма), чем известные условия. Из этих более общих условий, как частный случай, следуют известные условия. Показано, что новые условия могут приводить к неизвестным ранее процессам взаимодействия волн, в частности, при взаимодействии волн в плазме. Показано, що в розподілених системах існують більш загальні умови ефективної взаємодії хвиль (синхронізму), чим відомі умови. Із цих більш загальних умов, як окремий випадок, випливають відомі умови. Показано, що нові умови можуть приводити до невідомих раніше процесам взаємодії хвиль, зокрема, при взаємодії хвиль у плазмі.